Bipartite Recognition of DNA by TCF/Pangolin Is Remarkably Flexible and Contributes to Transcriptional Responsiveness and Tissue Specificity of Wingless Signaling. - Archbold, H.C.; Broussard, C.; Chang, M.V.; Cadigan, K.M. (PLoS Genetics, 2014)
The T-cell factor (TCF) family of transcription factors are major mediators of Wnt/?-catenin signaling in metazoans. All TCFs contain a High Mobility Group (HMG) domain that possesses specific DNA binding activity. In addition, many TCFs contain a second DNA binding domain, the C-clamp, which binds to DNA motifs referred to as Helper sites. While HMG and Helper sites are both important for the activation of several Wnt dependent cis-regulatory modules (W-CRMs), the rules of what constitutes a functional HMG-Helper site pair are unknown. In this report, we employed a combination of in vitro binding, reporter gene analysis and bioinformatics to address this question, using the Drosophila family member TCF/Pangolin (TCF/Pan) as a model. We found that while there were constraints for the orientation and spacing of HMG-Helper pairs, the presence of a Helper site near a HMG site in any orientation increased binding and transcriptional response, with some orientations displaying tissue-specific patterns. We found that altering an HMG-Helper site pair from a sub-optimal to optimal orientation/spacing dramatically increased the responsiveness of a W-CRM in several fly tissues. In addition, we used the knowledge gained to bioinformatically identify two novel W-CRMs, one that was activated by Wnt/?-catenin signaling in the prothoracic gland, a tissue not previously connected to this pathway. In sum, this work extends the importance of Helper sites in fly W-CRMs and suggests that the type of HMG-Helper pair is a major factor in setting the threshold for Wnt activation and tissue-responsiveness.